Legal Protection for Employees of Land Deed Officials in Submitting Applications for Transfer of Rights (Case Study of Cassation Decision 175/K/PDT/2021) - Amanda, Rizki; Tjempaka, Tjempaka (Journal of Law, Politic and Humanities, 2024)
This article is entitled legal protection for employees of land deed officials when submitting applications for transfer of rights . Using legal research methods with normative research types . With the results of the analysis, workers who work in PPAT or Notary offices have PKWT status, so the legal protection that can be provided by PPAT to these workers or employees depends on the policies provided by the employer, in this case namely PPAT. This is because the status of the job is PKWT, which means that the employer can be laid off at any time. This has implications for employees who carry out work on orders from their employers in situations where they commit unlawful acts, such as in the case of cassation decision 175/K/PDT/2021. Thus, juridically, it is a form of legal protection for employees who are in conflict with the law regarding their work due to orders from the employer, so the mandatory principle in work accountability does not apply, which has an impact on harming employees or workers in terms of responsibility for work actions.